(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
This article is a contribution to Postcolonial Trauma Studies. It aims to examine the ways in which Arab cultures bear the lasting aftereffects of the loss of al-Andalus that took place in 1492. Its focus is especially on the ramifications of such a key juncture in history that has enduringly contributed to the legitimation of the destruction of the Arab/Muslim cultures’ heritage. Western-centric knowledge came to license violence based on the demonization of the Other’s ways of knowing. Based on a postcolonial rethinking of trauma, the Arab cultures bear witness to the existence of the same discursive frameworks that made the destruction of the cultural heritage of al-Andalus possible.